Digital Da'wah and Religious Authority: A Narrative Review of Islamic Preaching in the Social Media Era - 'Ulyan, Mohammad (Sinergi International Journal of Islamic Studies, 2023)
This narrative review examines the transformative role of social media in contemporary Islamic preaching, focusing on Southeast Asia with an emphasis on Indonesia. The study aims to understand how digital platforms reshape da'wah practices, redefine religious authority, and facilitate inclusive discourse. Using a structured literature review method, sources were collected from databases including Scopus, Google Scholar, DOAJ, JSTOR, and ProQuest, employing keywords such as "digital da'wah," "Islamic preaching," and "social media and Islam." Inclusion criteria focused on peer-reviewed works published between 2010 and 2024, emphasizing digital religious practices in Muslim-majority contexts. The results show that social media enables visually engaging and emotionally resonant da'wah, increases interaction between preachers and audiences, and expands space for marginalized voices, including women and minority groups. Digital platforms have democratized Islamic discourse, disrupted traditional religious authority, and catalyzed reinterpretations of Islamic jurisprudence and gender roles. However, these advancements bring ethical and theological challenges, including misinformation, loss of scholarly oversight, and ideological polarization. National and local religious policies play a crucial role in shaping digital da'wah environments, either enabling or constraining its development. This review concludes that responsive religious policy and inclusive educational frameworks are essential to support ethical and effective digital da'wah. It recommends digital literacy integration in Islamic education, training for preachers, and further research into audience reception and global trends. As social media continues to influence Muslim religiosity, balanced approaches are necessary to sustain both innovation and theological integrity.